Pendekatan Contextual Teaching and Learning (Ctl) Pada Pembelajaran Volume Kubus Dan Balok Di Kelas V SD Dampak Transisi Pandemi Covid-19 Menuju Endemi - Isa, Muhammad; Hambali, Hambali; Zuhra, Intan (Jurnal Dedikasi Pendidikan, 2022)
This research is based on the problem of low student learning outcomes, during the transition from covid-19 to endemic, learning that is usually done is only teacher-centered because most learning is done online so that it affects the low learning outcomes of students, especially in learning the volume of cubes and blocks. This study aims to determine learning through the Contextual Teaching and Learning (CTL) approach in learning the material for the volume of cubes and blocks in fifth grade elementary school. This study uses a quantitative approach to the type of experimental research. The sample in this study was the fifth grade elementary school students, totaling 24 students consisting of 13 boys and 11 girls. Data was collected using observation sheets and tests (pretest and posttest). While the data processing is done by calculating the average value (x), S2 variance, standard deviation (S) and t test. The conclusion of the study shows that the Contextual Teaching and Learning (CTL) approach cannot improve student learning outcomes on the material for the volume of cubes and blocks in fifth grade elementary school during the Covid-19 transition to endemic. Learning activities carried out by teachers and students obtained a percentage rate of 87% (very good), and student learning completeness in the volume of cubes and blocks only 6 students or 25% of students achieved the Minimum Completeness Criteria